1994
DOI: 10.1128/jb.176.21.6464-6469.1994
|View full text |Cite
|
Sign up to set email alerts
|

Properties of two different Na+/H+ antiport systems in alkaliphilic Bacillus sp. strain C-125

Abstract: Na+/H+ antiport was studied in alkaliphilic Bacillus sp. strain C-125, its alkali-sensitive mutant 38154, and a transformant (pALK2) with recovered alkaliphily. The transformed was able to maintain an intracellular pH (pHin) that was lower than that of external milieu and contained an electrogenic Na+/H+ antiporter driven only by delta psi (membrane potential, interior negative). The activity of this delta psi-dependent Na+/H+ antiporter was highly dependent on pHin, increasing with increasing pHin, and was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…Ž . et al, 1994 and Bacillus sp Kitada et al, 1994 . The protons that exchange for Na q would presumably be exported by the electron transport system, which is responsible for generating the protonmotive force.…”
Section: Osmosensing and Osmoregulatory Compatible Solute Accumulatiomentioning
confidence: 99%
“…Ž . et al, 1994 and Bacillus sp Kitada et al, 1994 . The protons that exchange for Na q would presumably be exported by the electron transport system, which is responsible for generating the protonmotive force.…”
Section: Osmosensing and Osmoregulatory Compatible Solute Accumulatiomentioning
confidence: 99%
“…It was shown that the L11/1-dependent Na + jH + antiporter rather than the L1pH-dependent Na + jH + antiporter helps to maintain the intracellular pH around neutrality. 9) The cell wall negative charges and L11/1-dependent antiporter likely contribute to keeping the intracellular pH neutral when the organism grows in an alkaline environment. These functions are probably dependent on hydrogen ions generated by respiration and accumulated around the outer surface of the cytoplasmic membrane and in the cell-wall matrix.…”
mentioning
confidence: 99%
“…The cytoplasmic pH has also been measured from fluorescence quenching of 9-aminoacridine (Tsuchiya & Takeda, 1979;Sugiyama et al, 1985;Kitada et al, 1994). This pigment is retained effectively in cells whose cytoplasmic pH is lower than the extracellular pH.…”
Section: Measurement Of Cytoplasmic Ph and The Culture-phdependent Cymentioning
confidence: 99%